Dewatering Method For Food And Kitchen Waste - Nur Zawani Syifaa, Mohd Muzaini (Universiti Sains Malaysia, 2018)
Reduction of waste from the household can decrease the dependency and burden to landfills. Dewatering process is a method to separate liquid particles in food and kitchen scrap in order to reduce the amount of free and bound water appear in the component of food and plant. The purpose of the study is to determine the ability of domestic spin dryer to reduce the percentage of moisture content of kitchen waste by applying centrifugal force. The waste disposer used to break down the size of particles simplify separation process of liquid particles in solid particles. Type of typical food and kitchen waste in Malaysia are used as parameter in this project. Comparison of moisture level before and after dewatering process is determined to identify the different amount of moisture remain in waste after 5 minutes shredding and dewatering process. The waste loss during dewatering process also determined as an indicator of the effectiveness of this process in reducing the production of waste from source. The significant reduction about 50% -80% from initial weight of waste after 5 minutes dewatering shows this system is able to decrease waste production from the kitchen before being dumped to landfill. The product comes out from dewatering process can be decomposed and used in animal feeding production. The reaction of waste during composting process is observed to analyze the comparison of microbial growth during composting raw waste and dewatered waste. Based on the reduction of waste and composting, the dewatered process was considered as a suitable method used in solid waste management.